Research Developments on Arabic Learning Methods for Indonesians: Study Systematic Literature Review-Bibliometric Analysis: Perkembangan Penelitian tentang Metode Pembelajaran Bahasa Arab bagi Orang Indonesia: Kajian Systematic Literature Review-Analisis Bibliometrik - Slamet Riyadi; Hadi Munawwar; Faisal Ali A. Madkhali (ASSUNNAH PRESS, 2024)
There is no systematic mapping of the latest research in the field of learning Arabic for non-Arabic, in particular, that was published in SCOPUS as the top scientific publication. So often, there is a repetition of research that makes the disappearance of novelty in new research. The study aims at mapping, bothering, analyzing, and synthesizing studies related to learning Arabic for non-Arabic published in SCOPUS over the last five years. This research calls for the SLR or Systematic Literature Review method with a strongly qualitative approach. Data analysis uses bibliometric techniques using the Vos viewer application as a collection and description of the metadata of the last five years of research published by Scopus. It was concluded that Recommendations from this research encompass expanding research in Natural Language Processing (NLP), focusing on preschool stages, and fostering interdisciplinary collaboration among linguistics, information technology, developmental psychology, and education to formulate comprehensive and responsive approaches to Arabic language education tailored to learners' needs.